Pain intervention for failed conservative chronic pain treatment: The light at the end of the tunnel - Mohamed, Abdul Hadi; Abdullah, Nor Zamzila; Lukman, Mohd Fahmi; Ahmad, Mohd Ashri; Mat Nor, Mohd. Basri; Osman, Ariff (2011)

(untitled)
Chronic pain is a major public health problem that places serious stress on afflicted individuals and associated with deficits in quality of life, psychological adjustment, disability, reduced income potential, high levels of health care utilization and great loss to the nation as a whole. Chronic pain with the multitude of aetiologies is not only difficult to diagnose but also impose a great challenge in its management. Oral analgesics are considered as first-line therapy where stronger analgesics are used when pain control is not optimised. However, when pharmacological therapy or conventional surgery fails to control the pain, the role of minimally invasive interventional procedures become an option for the treatment of chronic pain. Interventional procedures target the neural structures that are presumed to mediate the experience of pain. This service is still very limited in our country as a result of limited expertise in this area. The Pain Management Clinic and Intervention Service at the International Islamic University Malaysia, Kuantan is one of the few centres in this country to have such a service. This service can be a niche area for research and a centre of excellence for our university in the future. We reported two classical cases of chronic pain that were treated with pain intervention to control severe pain after failing conservative management. After suffering for such a long period, these patients finally see lights at the end of the tunnel.